USING READING IN DETAIL TECHNIQUE TO IMPROVE STUDENTS’ SKILL IN READING RECOUNT TEXT - M. Fadhly Farhy Abbas; Masdelima Masdelima (Lectura : Jurnal Pendidikan, 2018)
In this research, the researcher found the students’ problem in reading comprehension of recount text. The problem was the students still had difficulties to determine generic structure (Orientation, Event, Re-Orientation), social function and language features when they read recount text and did the random text of recount text. The purpose of this research was to improve students’ reading comprehension of recount text at class VIII of MTs Ummi Fatimah Pekanbaru and what factors influence it. This research was Clasroom Action Research (CAR). The number of participants were 19 students. The researcher used test, observation sheets, field notes, and interview to collect the data. The result of this research showed that the students’ average in based score was 71,05, in cycle I was 82,63. The average in cycle I could achieve the passing grade score is 75. It was found that some factors that influence the students’ improvement in reading comprehension on recount text by using Reading in Detail Technique were Reading in Detail Technique facilitating students to know, understand and determine generic structure, and language features of recount text when they applied it with their discussion group. And also the interesting materials of recount text helped students understand better like experience, event, etc. In conclution the use of Reading in Detail Technique can improve reading comprehension of recount text at class VIII of MTs Ummi Fatimah Pekanbaru.